Complexation of enalapril maleate with beta-cyclodextrin: NMR spectroscopic study in solution - Syed Mashhood Ali; Arti Maheshwari; Fahmeena Asmat; Mamoru Koketsu (Química Nova, 2006)
A detailed NMR (¹H , COSY, ROESY) spectroscopic study of complexation of enalapril maleate with beta-cyclodextrin was carried out. The ¹H NMR spectrum of enalapril maleate confirmed the existence of cis-trans equilibrium in solution, possibly due to hindered rotation along the amide bond. The cis-trans ratio remained almost the same in the presence of beta-cyclodextrin but in one case it was found significantly different which suggests a catalytic role of beta-cyclodextrin in the isomerization. ¹H NMR titration studies confirmed the formation of an enalapril-beta-cyclodextrin inclusion complex as evidenced by chemical shift variations in the proton resonances of both the host and the guest. The stoichiometry of the complex was determined to be 2:1 (guest: host). The mode of penetration of the guest into the beta-cyclodextrin cavity as well as the structure of the complex were established using ROESY spectroscopy.